A Fluorescence-Detected Coordination-Induced Spin State Switch - Kurz, Hannah; Schoetz, Konstantin; Papadopoulos, Ilias; Heinemann, Frank Wilhelm; Maid, Harald; Guldi, Dirk Michael; Koehler, Anna; Hoerner, Gerald; Weber, Birgit (Journal of the American Chemical Society, 2021)
The response of the spin state to in situ variation of the coordination number (CISSS) is a promising and viable approach to smart sensor materials, yet it suffers to date from insensitive detection. Herein, we present the synthetic access to a family of planar nickel(II) complexes, whose CISSS is sensitively followed by means of fluorescence detection. For this purpose, nickel(II) complexes with four phenazine-based Schiff base-like ligands were synthesized and characterized through solution-phase spectroscopy (NMR and UV-vis), solid-state structure analysis (single-crystal XRD), and extended theoretical modeling. All of them reveal CISSS in solution through axial ligating a range of N- and O-donors. CISSS correlates nicely with the basicity of the axial ligand and the substitution-dependent acidity of the nickel(II) coordination site. Remarkably, three out of the four nickel(II) complexes are fluorescent in noncoordinating solvents but are fluorescence-silent in the presence of axial ligands such as pyridine. As these complexes are rare examples of fluorescent nickel(II) complexes, the photophysical properties with a coordination number of 4 were studied in detail, including temperature-dependent lifetime and quantum yield determinations. Most importantly, fluorescence quenching upon adding axial ligands allows a "black or white", i.e. digital, sensoring of spin state alternation. Our studies of fluorescence-detected CISSS (FD-CISSS) revealed that absorption-based CISSS and FD-CISSS are super proportional with respect to the pyridine concentration: FD-CISSS features a higher sensitivity. Overall, our findings indicate a favored ligation of these nickel(II) complexes in the excited state in comparison to the ground state.
CRIS-Team WoS Importer:2021-03-26

Altering singlet fission pathways in perylene-dimers; perylene-diimide versus perylene-monoimide - Papadopoulos, Ilias; Gutierrez-Moreno, David; Bo, Yifan; Casillas, Ruben; Greißel, Phillip; Clark, Timothy; Fernandez-Lazaro, Fernando; Guldi, Dirk Michael (Nanoscale, 2022)
We used a systematic approach to shed light on the inherent differences in perylenes, namely monoimides versus diimides, including coplanarity and dipole moment, and their impact on singlet fission (SF) by designing, synthesizing, and probing a full fledged series of phenylene- and naphthalene-linked dimers. Next to changing the functionality of the perylene core, we probed the effect of the spacers and their varying degrees of rotational freedom, molecular electrostatic potentials, and intramolecular interactions on the SF-mechanism and -efficiencies. An arsenal of spectroscopic techniques revealed that for perylene-monoimides, a strong charge-transfer mixing with the singlet and triplet excited states restricts SF and yields low triplet quantum yields. This is accompanied by an up-conversion channel that includes geminate triplet-triplet recombination. Using perylene-diimides alters the SF-mechanism by populating a charge-separated-state intermediate, which either favors or shuts-down SF. Napthylene-spacers bring about higher triplet quantum yields and overall better SF-performance for all perylene-monoimides and perylene-diimides. The key to better SF-performance is rotational freedom because it facilitates the overall excited-state polarization and amplifies intramolecular interactions between chromophores.
CRIS-Team WoS Importer:2022-04-08

Catalyzing Singlet Fission by Transition Metals: Second versus Third Row Effects - Hou, Yuxuan; Papadopoulos, Ilias; Bo, Yifan; Wollny, Anna-Sophie; Ferguson, Michael J.; Mai, Lukas; Tykwinski, Rik R.; Guldi, Dirk Michael (Precision Chemistry, 2023)
The synthesis and characterization of platinum(II) and palladium(II) complexes bearing two (dimers Pt(Lpc)2Cl2 and Pd(Lpc)2Cl2), one (monomers Pt(Lpc)(Lref)Cl2 and Pd(Lpc)(Lref)-Cl2), or no (reference compounds Pt(Lref)2Cl2 and Pd(Lref)2Cl2) pentacene-based pyridyl ligands are presented. Photophysical properties of the dimers are probed by means of steady-state and time-resolved transient absorption measurements in comparison to the monomer and model compounds. Our results document that despite enhanced spin-orbit coupling from the presence of heavy atoms, intramolecular singlet fission (iSF) is not challenged by intersystem crossing. iSF thus yields correlated triplet pairs and even uncorrelated triplet excited states upon decoherence. Importantly, significant separation of the two pentacenyl groups facilitates decoupling of the two chromophores. Furthermore, the mechanism of iSF is altered depending on the respective metal center, that is, Pt(II) versus Pd(II). The dimer based on Pt(II), Pt(Lpc)2Cl2, exhibits a direct pathway for the iSF and forms a correlated triplet pair with singlet-quintet spin-mixing within 10 ns in variable solvents. On the other hand, the dimer based on Pd(II), Pd(Lpc)2Cl2, leads to charge transfer mixing during the population of the correlated triplet pair that is dependent on solvent polarity. Moreover, Pd(Lpc)2Cl2 gives rise to a stable equilibrium between singlet and quintet correlated triplet pairs with lifetimes of up to 170 ns. Inherent differences in the size and polarizability, when contrasting platinum(II) with palladium(II), are the most likely rationale for the underlying trends.
CRIS-Team Scopus Importer:2024-12-16
Keywords: electronic coupling; metal complexes; pentacene dimers; singlet fission; ultrafast spectroscopy

Collecting up to 115% of Singlet-Fission Products by Single-Walled Carbon Nanotubes - Menon, Arjun; Papadopoulos, Ilias; Harreiß, Christina; Mora-Fuentes, Juan P.; Cortizo-Lacalle, Diego; Mateo-Alonso, Aurelio; Spiecker, Erdmann; Guldi, Dirk Michael (Acs Nano, 2020)
In this contribution, we focused on integrating a phenylene-bridged dibenzodiazahexacene dimer (o-DAD), which is singlet fission (SF) active, onto single-walled carbon nanotubes (SWCNTs) as a low-energy sink for energetically low lying excited states that stem from SF. Spectroscopic and microscopic assays assisted in documenting that SWCNT/o-DAD feature high stability in THF as a result of electronic interactions between the individual constituents. For example, statistical Raman analysis underlined n-doping of SWCNTs in the presence of o-DAD. Fluorescence spectroscopy prompted an energy transfer between the individual constituents, a conclusion that was exclusively derived from the quenching of the o-DAD-centered fluorescence. Excitation spectroscopy with a focus on the SWCNT fluorescence confirmed independently this conclusion by showing o-DAD-centered features. Our work was rounded off by time-resolved transient absorption measurements with SWCNT/o-DAD, in which evidence was gathered for the sequential o-DAD-centered SF with an efficiency of 112% followed by a unidirectional energy transfer from o-DAD to SWCNT and a rapid deactivation. The energy transfer efficiency from SF products such as (S1S0)CT and 1(T1T1) exceeded the 100% threshold with values of 115%, which is conventionally found in energy transfer scheme
Keywords: carbon nanotubes; pyrene-fused azaacenes; singlet fission; energy transfer; doping

Controlling Intramolecular Förster Resonance Energy Transfer and Singlet Fission in a Subporphyrazine–Pentacene Conjugate by Solvent Polarity - Guzman, David; Papadopoulos, Ilias; Lavarda, Giulia; Rami, Parisa R.; Tykwinski, Rik R.; Rodriguez-Morgade, M. Salome; Guldi, Dirk Michael; Torres, Tomas (Angewandte Chemie International Edition, 2020)
Due its complementary absorptions in the range of 450 and 600 nm, an energy-donating hexaaryl-subporphyrazine has been linked to a pentacene dimer, which acts primarily as an energy acceptor and secondarily as a singlet fission enabler. In the corresponding conjugate, efficient intramolecular Förster resonance energy transfer (i-FRET) is the modus operandi to transfer energy from the subporphyrazine to the pentacene dimer. Upon energy transfer, the pentacene dimer undergoes intramolecular singlet fission (i-SF), that is, converting the singlet excited state, via an intermediate state, into a pair of correlated triplet excited states. Solvatochromic fluorescence of the subporphyrazine is a key feature of this system and features a red-shift as large as 20 nm in polar media. Solvent is thus used to modulate spectral overlap between the fluorescence of subporphyrazine and absorption of the pentacene dimer, which controls the Förster rate constant, on one hand, and the triplet quantum yield, on the other hand. The optimum spectral overlap is realized in xylene, leading to Förster rate constant of 3.52×1011 s−1 and a triplet quantum yield of 171 % ±10 %. In short, the solvent polarity dependence, which is a unique feature of subporphyrazines, is decisive in terms of adjusting spectral overlap, ensuring a sizable Förster rate constant, and maximizing triplet quantum yields. Uniquely, this optimization can be achieved without a need for synthetic modification of the subporphyrazine donor.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Förster resonance energy transfer; intramolecular singlet fission; subporphyrazine

Efficient charge-transfer from diketopyrrolopyrroles to single-walled carbon nanotubes - Papadopoulos, Ilias; Menon, Arjun; Plass, Fabian; Molina, Desire; Harreiß, Christina; Kahnt, Axel; Spiecker, Erdmann; Sastre-Santos, Angela; Guldi, Dirk Michael (Nanoscale, 2021)
In this contribution, the excited state charge-transfer interactions between single-walled carbon nanotubes (SWCNTs) and a variety of phenyl, 4-bromophenyl, and thiophene substituted diketopyrrolopyrroles (DPPs), is described. Atomic force microscopy (AFM) and aberration corrected high resolution transmission electron microscopy (AC-HRTEM) corroborated the successful formation of DPP/SWCNTs. Steady-state absorption, fluorescence, and Raman spectroscopies all gave insights into the impact on their ground and excited states as well as on the nature of their electronic communication/interaction. Of great value was time-resolved transient absorption spectroscopy on the femto- and nanosecond time-scales; it assisted in deciphering the charge-transfer mechanism from the DPPs to the SWCNT and in analyzing the dynamics thereof with transfer efficiencies of up to 81%. Important confirmation for the one-electron oxidized DPPs came from pulse radiolysis assays with focus on establishing their spectral fingerprints. Our full-fledged work demonstrates that the successful preparation of stable DPP/SWCNTs represents an important step towards establishing them as a viable alternative to porphyrin-based systems in emerging applications such as solar energy conversion.
CRIS-Team WoS Importer:2021-07-16

Förster Resonance Energy Transfer Sensitized Singlet Fission in BODIPY-Pentacene Dimer Conjugates - Wollny, Anna-Sophie; Lavarda, Giulia; Papadopoulos, Ilias; López-Duarte, Ismael; Gotfredsen, Henrik; Hou, Yuxuan; Tykwinski, Rik R.; Torres, Tomás; Guldi, Dirk Michael (Advanced Optical Materials, 2023)
In the present work, the energy donor 4,4-difluoro-4-bora-3a,4a-diaza-s-indacene (BODIPY) is used for the first time in combination with a pentacene dimer (Pnc2) to provide the conjugate BODIPYPnc2 that features absorption throughout a large part of the solar spectrum. Upon photoexcitation, the singlet excited state energy of BODIPY is transferred to the pentacene dimer via intramolecular Förster resonance energy transfer (FRET). Subsequently, the pentacene dimer undergoes intramolecular singlet fission. In this process, a singlet correlated triplet pair is generated from the first singlet excited state via coupling to an intermediate state. The results show that solvent polarity has an influence on the system, with the largest FRET rate (i.e., 7.46 × 1011 s−1) being obtained in the most polar solvent (namely, benzonitrile) along with the largest triplet quantum yield (i.e., 207 ± 20%).
CRIS-Team Scopus Importer:2023-10-13
Keywords: BODIPY; down conversion; energy transfer; pentacene; photoenergy conversion; singlet fission; time-resolved spectroscopy

Harnessing multiple generated excitons from intermolecular singlet fission of perylene–monoimides in a p-type dye-sensitized solar cell - Papadopoulos, Ilias; Schol, Peter; Garcés-Garcés, Jose; Sastre-Santos, Ángela; Fernández-Lázaro, Fernando; Guldi, Dirk Michael (Solar Energy, 2023)
A perylene-monoimide (PMI) monomer is functionalized with a benzoic acid to support immobilization on copper oxide (CuO) / nickel oxide (NiO) p-type semiconductors in order to construct p-type dye-sensitized solar cells (DSSCs). All devices are fully characterized by means of J-V, electrochemical impedance, and incident photon-to-current conversion efficiency (IPCE) measurements. Their optimization in terms of PMI uptake, iodine / Li+ addition and layer thickness lead to efficiencies as high as 0.07 %. For PMIs, the favorable relationship between their respective singlet and triplet excited state energies of 2.36 and 1.12 eV enable thermodynamically driven singlet fission (SF). The strong inter–PMI interactions on the semiconductor surface allow for an efficient and fast intermolecular SF. The formed correlated triplet pair ((T1)(T1)) is corroborated by means of time-resolved transient absorption spectroscopy (TAS) and partakes in an interfacially charge injection into the CuO / NiO semiconductors within the p-type DSSCs.
CRIS-Team Scopus Importer:2023-01-13
Keywords: Intermolecular singlet fission; P-type dye sensitized solar cells; Perylene-monoimides; Time-resolved spectroscopy

How To Make Nitroaromatic Compounds Glow: Next-Generation Large X-Shaped, Centrosymmetric Diketopyrrolopyrroles - Skonieczny, Kamil; Papadopoulos, Ilias; Thiel, Dominik; Gutkowski, Krzysztof; Haines, Philipp; McCosker, Patrick Michael; Laurent, Adele D.; Keller, Paul A.; Clark, Timothy; Jacquemin, Denis; Guldi, Dirk Michael; Gryko, Daniel T. (Angewandte Chemie International Edition, 2020)
Red-emissive pi-expanded diketopyrrolopyrroles (DPPs) with fluorescence reaching lambda=750 nm can be easily synthesized by a three-step strategy involving the preparation of diketopyrrolopyrrole followed by N-arylation and subsequent intramolecular palladium-catalyzed direct arylation. Comprehensive spectroscopic assays combined with first-principles calculations corroborated that both N-arylated and fused DPPs reach a locally excited (S-1) state after excitation, followed by internal conversion to states with solvent and structural relaxation, before eventually undergoing intersystem crossing. Only the structurally relaxed state is fluorescent, with lifetimes in the range of several nanoseconds and tens of picoseconds in nonpolar and polar solvents, respectively. The lifetimes correlate with the fluorescence quantum yields, which range from 6 % to 88 % in nonpolar solvents and from 0.4 % and 3.2 % in polar solvents. A very inefficient (T-1) population is responsible for fluorescence quantum yields as high as 88 % for the fully fused DPP in polar solvents.
CRIS-Team WoS Importer:2020-07-24

Influence of the heavy-atom effect on singlet fission: A study of platinum-bridged pentacene dimers - Basel, Bettina; Young, Ryan M.; Krzyaniak, Matthew D.; Papadopoulos, Ilias; Hetzer, Constantin; Gao, Yueze; La Porte, Nathan T.; Phelan, Brian T.; Clark, Timothy; Tykwinski, Rik R.; Wasielewski, Michael R.; Guldi, Dirk Michael (Chemical Science, 2019)
The process of singlet fission (SF) produces two triplet excited states (T1 + T1) from one singlet excited exciton (S1) and a molecule in its ground state (S0). It, thus, possesses the potential to boost the solar cell efficiency above the thermodynamic Shockley-Queisser limit of 33%. A key intermediate in the SF mechanism is the singlet correlated triplet pair state 1(T1T1). This state is of great relevance, as its formation is spin-allowed and, therefore, very fast and efficient. Three fundamentally different pathways to formation of 1(T1T1) have been documented so far. The factors that influence which mechanism is associated with which chromophore, however, remain largely unknown. In order to harvest both triplet excitons independently, a decorrelation of the correlated triplet pair state to two individual triplets is required. This second step of the SF process implies a change in the total spin quantum number. In the case of a dimer, this is usually only possible if the coupling between the two pentacenes is sufficiently weak. In this study, we present two platinum-bridged pentacene dimers in which the pentacenes are coupled strongly, so that spin-decorrelation yielding (T1 + T1) was initially expected to be outcompeted by triplet-triplet annihilation (TTA) to the ground state. Both platinum-bridged pentacene dimers undergo quantitative formation of the (T1T1) state on a picosecond timescale that is unaffected by the internal heavy-atom effect of the platinum. Instead of TTA of (T1T1) to the ground state, the internal heavy-atom effect allows for 1(T1T1)-3(T1T1) and 1(T1T1)-5(T1T1) mixing and, thus, triggers subsequent TTA to the (T1S0) state and minor formation of (T1 + T1). A combination of transient absorption and transient IR spectroscopy is applied to investigate the mechanism of the (T1T1) formation in both dimers. Using a combination of experiment and quantum chemical calculations, we are able to observe a transition from the CT-mediated to the direct SF mechanism and identify relevant factors that influence the mechanism that dominates SF in pentacene. Moreover, a combination of time-resolved optical and electron paramagnetic resonance spectroscopic data allows us to develop a kinetic model that describes the effect of enhanced spin-orbit couplings on the correlated triplet pair state.
CRIS-Team Scopus Importer:2019-12-31

Intramolecular Triplet Diffusion Facilitates Triplet Dissociation in a Pentacene Hexamer - Greißel, Phillip; Thiel, Dominik; Gotfredsen, Henrik; Chen, Lan; Krug, Marcel; Papadopoulos, Ilias; Miskolzie, Mark; Torres, Tomás; Clark, Timothy; Brøndsted Nielsen, Mogens; Tykwinski, Rik R.; Guldi, Dirk Michael (Angewandte Chemie International Edition, 2024)
Triplet dynamics in singlet fission depend strongly on the strength of the electronic coupling. Covalent systems in solution offer precise control over such couplings. Nonetheless, efficient free triplet generation remains elusive in most systems, as the intermediate triplet pair 1(T1T1) is prone to triplet-triplet annihilation due to its spatial confinement. In the solid state, entropically driven triplet diffusion assists in the spatial separation of triplets, resulting in higher yields of free triplets. Control over electronic coupling in the solid state is, however, challenging given its sensitivity to molecular packing. We have thus developed a hexameric system (HexPnc) to enable solid-state-like triplet diffusion at the molecular scale. This system is realized by covalently tethering three pentacene dimers to a central subphthalocyanine scaffold. Transient absorption spectroscopy, complemented by theoretical structural optimizations and steady-state spectroscopy, reveals that triplet diffusion is indeed facilitated due to intramolecular cluster formation. The yield of free triplets in HexPnc is increased by a factor of up to 14 compared to the corresponding dimeric reference (DiPnc). Thus, HexPnc establishes crucial design aspects for achieving efficient triplet dissociation in strongly coupled systems by providing avenues for diffusive separation of 1(T1T1), while, concomitantly, retaining strong interchromophore coupling which preserves rapid formation of 1(T1T1).
CRIS-Team Scopus Importer:2024-02-23
Keywords: Oligoacene; Photoenergy Conversion; Singlet Fission; Triplet Dissociation; Ultrafast Spectroscopy

Light-harvesting porphyrazines to enable intramolecular singlet fission - Medina, Diana Paola; Papadopoulos, Ilias; Lavarda, Giulia; Gotfredsen, Henrik; Rami, Parisa R.; Tykwinski, Rik R.; Rodríguez-Morgade, M. Salomé; Guldi, Dirk Michael; Torres, Tomás (Nanoscale, 2019)
A porphyrazine featuring complementary absorption to a pentacene dimer was chosen to fill the absorption gap of the latter in the range of 450 to 600 nm to realize panchromatic absorption through the visible region out to ca. 700 nm. Of even greater relevance is the quantitative intramolecular Förster resonance energy transfer (i-FRET) to funnel energy to the pentacene moieties, where efficient intramolecular singlet fission (i-SF) converts the singlet excited state into the corresponding triplet excited states. Remarkably, the triplet quantum yield either via direct excitation or via indirect i-FRET is up to 200% ± 20% in polar solvents.
CRIS-Team Scopus Importer:2019-12-10

Modulating the dynamics of Forster resonance energy transfer and singlet fission by variable molecular spacers - Zirzlmeier, Johannes; Lavarda, Giulia; Gotfredsen, Henrik; Papadopoulos, Ilias; Chen, Lan; Clark, Timothy; Tykwinski, Rik R.; Torres, Tomas; Guldi, Dirk Michael (Nanoscale, 2020)
In contrast to previous work, the synergy between panchromatic absorption and molecular singlet fission (SF) is exploited to optimize solar energy conversion through evaluation of the distance dependence of intramolecular Forster Resonance Energy Transfer (i-FRET) in a series of subphthalocyanines (SubPcs) linked to pentacene dimers (Pnc(2)s). To provide control over i-FRET, the molecular spacer rather than the energy donating SubPc is tailored in the corresponding SubPc-Pnc(2) conjugates in terms of length (i.e., the number of aryl units) and flexibility (i.e., presence or absence of a CH2 group). AM1-CIS calculations support the experiments, which underline the importance of the molecular spacer to impact not only the i-FRET dynamics, but also the dynamics of intramolecular singlet fission (i-SF). For example, an additional phenyl group slows down both i-FRET and i-SF by a factor of similar to 3.8 and similar to 1.6, respectively, by a quinone-like conjugation pattern that affords a pentacene acceptor orbital that is fairly delocalized over both pentacenes and the bridging phenyl.
CRIS-Team WoS Importer:2020-12-11

Molecular insights and concepts to engineer singlet fission energy conversion devices - Casillas, Ruben; Papadopoulos, Ilias; Ullrich, Tobias; Thiel, Dominik; Kunzmann, Andreas; Guldi, Dirk Michael (Energy and Environmental Science, 2020)
In thisReview, we showcase the fundamental processes of intermolecular and intramolecular singlet fission (SF). Furthermore we prioritize the information, which is relevant for the implementation of SF and SF-materials into solar energy conversion devices. We do this, firstly, by referring to the complexity of SF, and discussing key aspects of it; secondly, by mentioning the instrumental efforts, which assisted in unraveling SF in benchmark molecular building blocks such as tetracene, pentacene, and their corresponding dimers/oligomers; thirdly, by presenting a collection of SF-materials, as well as available photophysical and electrochemical data for energy conversion research. Among others, these include perylene-diimides (PDIs), diketopyrrolopyrroles (DPPs), carotenoids, conjugated polymers, and diradicaloids. This Review is rounded off by discussing pioneering contributions of SF in solar energy conversion schemes and highlighting recent developments in the field. Overall, a set of guidelines is given for new directions in SF, that is, the use of new tools to discover new SF-materials (i.e.spectroscopy, computation, machine-learning) and deposition processes (i.e.thin-films, DSSCs, OPVs) to couple SF-materials with the appropriate semiconductors.
CRIS-Team WoS Importer:2020-10-02

Parallel versus Twisted Pentacenes: Conformational Impact on Singlet Fission - Papadopoulos, Ilias; Reddy, S. Rajagopala; Coto, Pedro B.; Lehnherr, Dan; Thiel, Dominik; Thoss, Michael; Tykwinski, Rik R.; Guldi, Dirk Michael (Journal of Physical Chemistry Letters, 2022)
We placed two pentacene chromophores at the termini of a diacetylene linker to investigate the impact of excitation wavelength, conformational flexibility, and vibronic coupling on singlet fission. Photoexcitation of the low-energy absorption results in a superposed mixture of states, which transform on an ultrafast time-scale into a spin-correlated and vibronically coupled/hot delocalized triplet pair 1(T1T1)deloc. Regardless of temperature, the lifetime for 1(T1T1)deloc is less than 2 ps. In contrast, photoexcitation of the high-energy absorption results in the formation of 1(T1T1)deloc lasting 1.0 ps, which then decays at room temperature within 4 ps via triplet-triplet annihilation. Lowering the temperature enables 1(T1T1)deloc to delocalize and vibronically decouple, in turn affording 1(T1T1)loc. In addition, our results suggest that the quasi-free rotation at the diacetylene spacer may lead to twisted conformations with very low SF quantum yields, highlighting the need of controlling this structural aspect in the design of new singlet fission active molecules.
CRIS-Team Scopus Importer:2023-03-07

Pentacenes: A Molecular Ruler for Singlet Fission - Basel, Bettina; Papadopoulos, Ilias; Thiel, Dominik; Casillas, Ruben; Zirzlmeier, Johannes; Clark, Timothy; Guldi, Dirk Michael; Tykwinski, Rik R. (Trends in Chemistry, 2019)
Surpassing the Shockley–Queisser limit, which places an upper bound on solar conversion efficiency for a single p–n junction solar cell at slightly more than 30%, is one of the grand challenges in the field of solar-energy research. Singlet fission (SF)in molecular acenes, the molecular analog of multiple exciton generation (MEG), has the potential to initiate a game-changing advance in solar-energy conversion. SF allows singlet-excited states (S 1 )to be down-converted into twice as many triplet-excited states (T 1 ).
CRIS-Team Scopus Importer:2019-05-14
Keywords: interfacial electron transfer; pentacenes; singlet fission; solar energy; time-resolved spectroscopy; triplet

Perylene-Monoimides: Singlet Fission Down-Conversion Competes with Up-Conversion by Geminate Triplet-Triplet Recombination - Papadopoulos, Ilias; Gutiérrez-Moreno, David; McCosker, Patrick Michael; Casillas, Ruben; Keller, Paul A.; Sastre-Santos, Ángela; Clark, Timothy; Fernández-Lázaro, Fernando; Guldi, Dirk Michael (Journal of Physical Chemistry A, 2020)
Triplet-excited-state energies of perylene-monoimides (PMIs) lie in the range 1.12 eV ± 2 meV when compared to singlet-excited-state energies of about 2.39 eV ± 2 meV; therefore, the corresponding naphthalene-linked PMI-Dimer was investigated as a novel singlet-fission (SF) material. Ultrafast transient absorption measurements demonstrated the (S1S0)-to-1(T1T1) transformation and the involvement of a mediating step in the overall 1(T1T1) formation. The intermediate is a charge-transfer state that links the initial (S1S0) with the final 1(T1T1), and imposes charge-transfer character on both, which are thus denoted (S1S0)CT and 1(T1T1)CT. At room temperature, the decorrelation and stability of 1(T1T1)CT is affected by the geminate triplet-triplet recombination (G-TTR) of the two triplets. Independent confirmation for G-TTR to afford up-converted (S1S0)UC in fsTA and nsTA measurements with PMI-Dimer, came from probing PMI-Monomer (T1)s in triplet-triplet annihilation up-conversion (TTA-UC). The G-TTR channel, active in the PMI-Dimer at room temperature, is suppressed by working at either low temperatures (∼140 K) or in polar solvents (benzonitrile): Both scenarios assist in stabilizing (T1T1)CT. As a consequence, the triplet quantum yields are 4.2% and 14.9% at room temperature and 140 K, respectively, in 2-methyltetrahydrofuran.
CRIS-Team Scopus Importer:2020-07-31

Photophysical characterization of a ruthenium-based tetrameric pentacene complex - Hou, Yuxuan; Papadopoulos, Ilias; Ferguson, Michael J.; Jux, Norbert; Tykwinski, Rik R.; Guldi, Dirk Michael (Journal of Porphyrins and Phthalocyanines, 2023)
The synthesis of a ruthenium(II) tetramer (Ru(Lpc)4Cl2) bearing pyridyl pentacene-based ligands and its corresponding model complex lacking pentacene moieties (Ru(Lref)4Cl2) is presented. The formation of these tetramers is corroborated by 1H, 13C NMR, and IR spectroscopies, as well as X-ray crystallography and mass spectrometry. Photophysical properties of the tetramers are probed by steady-state and time-resolved transient absorption spectroscopy. Steady-state absorption and fluorescence assays suggest weak ground-state interactions between the pentacene moieties of Ru(Lpc)4Cl2 and sizeable metal-to-ligand interactions, which are ruthenium-to-pentacene based. Time-resolved transient absorption measurements reveal an ultrafast singlet-to-triplet transition that occurs on the femtosecond timescale and that yields vibrationally hot and solvent unrelaxed triplet excited states. After relaxation, these triplet excited states deactivate back to the ground state in less than 3 μs. These observations lead us to conclude that intersystem crossing outperforms photophysical processes such as singlet fission.
CRIS-Team Scopus Importer:2023-05-26
Keywords: excited state dynamics; intersystem crossing; pentacene; ruthenium complex; singlet fission

Photoreactions of Sc3N@C80 with Disilirane, Silirane, and Digermirane: A Photochemical Method to Separate Ih and D5h Isomers - Kako, Masahiro; Miyabe, Kyosuke; Fukazawa, Shinpei; Kanzawa, Shinji; Yasui, Masanori; Yamada, Michio; Maeda, Yutaka; Slanina, Zdeněk; Uhlík, Filip; Adamowicz, Ludwik; Papadopoulos, Ilias; Guldi, Dirk Michael; et al. (Photochem, 2022)
Under photoirradiation, Sc3N@Ih-C80 reacted readily with disilirane 1, silirane 4, and digermirane 7 to afford the corresponding 1:1 adducts, whereas Sc3N@D5h-C80 was recovered without producing those adducts. Based on these results, we described a novel method for the exclusive separation of Ih and D5h isomers of Sc3N@C80. The method includes three procedures: selective derivatization of Sc3N@Ih-C80 using 1, 4, and 7, facile HPLC separation of pristine Sc3N@D5h-C80 and Sc3N@Ih-C80 derivatives, and thermolysis of Sc3N@Ih-C80 derivatives to collect pristine Sc3N@Ih-C80. In addition, laser flash photolysis experiments were conducted to elucidate the reaction mechanism. Decay of the transient absorption of 3Sc3N@Ih-C80* was observed to be enhanced in the presence of 1, indicating the quenching process. When Sc3N@D5h-C80 was used, the transient absorption was much less intensive. Therefore, the quenching of 3Sc3N@D5h-C80* by 1 could not be confirmed. Furthermore, we applied time-dependent density functional theory (TD-DFT) calculations of the photoexcited states of Sc3N@C80 to obtain insights into the reaction mechanism.
CRIS-Team Scopus Importer:2024-12-16
Keywords: density functional theory; digermirane; disilirane; metallofullerene; photophysics; Sc; silirane

Sensitized Singlet Fission in Rigidly Linked Axial and Peripheral Pentacene-Subphthalocyanine Conjugates - Gotfredsen, Henrik; Thiel, Dominik; Greißel, Phillip; Chen, Lan; Krug, Marcel; Papadopoulos, Ilias; Ferguson, Michael J.; Nielsen, Mogens Brøndsted; Torres, Tomas; Clark, Timothy; Guldi, Dirk Michael; Tykwinski, Rik R. (Journal of the American Chemical Society, 2023)
The goal of harnessing the theoretical potential of singlet fission (SF), a process in which one singlet excited state is split into two triplet excited states, has become a central challenge in solar energy research. Covalently linked dimers provide crucial models for understanding the role of chromophore arrangement and coupling in SF. Sensitizers can be integrated into these systems to expand the absorption bandwidth through which SF can be accessed. Here, we define the role of the sensitizer-chromophore geometry in a sensitized SF model system. To this end, two conjugates have been synthesized consisting of a pentacene dimer (SF motif) connected via a rigid alkynyl bridge to a subphthalocyanine (the sensitizer motif) in either an axial or a peripheral arrangement. Steady-state and time-resolved photophysical measurements are used to confirm that both conjugates operate as per design, displaying near unity energy transfer efficiencies and high triplet quantum yields from SF. Decisively, energy transfer between the subphthalocyanine and pentacene dimer occurs ca. 26 times faster in the peripheral conjugate, even though the two chromophores are ca. 3 angstrom farther apart than in the axial conjugate. Following a theoretical evaluation of the dipolar coupling, Vdip2, and the orientation factor, kappa 2, of both the axial (Vdip2 = 140 cm-2; kappa 2 = 0.08) and the peripheral (Vdip2 = 724 cm-2; kappa 2 = 1.46) arrangements, we establish that this rate acceleration is due to a more favorable (nearly co-planar) relative orientation of the transition dipole moments of the subphthalocyanine and pentacenes in the peripheral constellation.
CRIS-Team WoS Importer:2023-05-19

Singlet Fission in Enantiomerically Pure Pentacene Dimers - Papadopoulos, Ilias; Gao, Yueze; Hetzer, Constantin; Tykwinski, Rik R.; Guldi, Dirk Michael (Chemphotochem, 2020)
Singlet fission (SF), that is, producing two triplet excited states (T-1+T-1) from a single singlet excited state (S1S0), has the potential to surpass the thermodynamic Shockley-Queisser limit for solar cells of 33 %. Of great relevance for singlet fission is the (S1S0)-to-(1)(T1T1) transformation as it is the key step in driving the efficiency of SF. In the current study, we focus on the control over intramolecular interactions in enantiomerically pure platinum linked pentacene dimers, (S,S)- and (R,R)-cis-Pt. Despite the internal heavy-atom effect stemming from the presence of the Pt-centered linkers, (S,S)- and (R,R)-cis-Pt undergo quantitative and solvent dependent formation of (1)(T1T1). Implicit is an enantiomer-independent SF mediation by means of a virtual CT intermediate in a superexchange mechanism. With the help of steady-state and time-resolved spectroscopic techniques, a kinetic model is developed to describe the entire deactivation pathway following photoexcitation of (S,S)- and (R,R)-cis-Pt.
CRIS-Team WoS Importer:2020-05-02

Singlet Fission in Pyrene-Fused Azaacene Dimers - Mora-Fuentes, Juan P.; Papadopoulos, Ilias; Thiel, Dominik; Alvarez-Boto, Roberto; Cortizo-Lacalle, Diego; Clark, Timothy; Melle-Franco, Manuel; Guldi, Dirk Michael; Mateo-Alonso, Aurelio (Angewandte Chemie International Edition, 2019)
Singlet fission has emerged as a promising strategy to avoid the loss of extra energy through thermalization in solar cells. A family of dimers consisting of nitrogen-doped pyrene-fused acenes that undergo singlet fission with triplet quantum yields as high as 125 % are presented. They provide new perspectives for nitrogenated polycyclic aromatic hydrocarbons and for the design of new materials for singlet fission.
CRIS-Team WoS Importer:2019-12-10

Solution-based intramolecular singlet fission in cross-conjugated pentacene dimers - Zirzlmeier, Johannes; Casillas, Ruben; Reddy, Rajagopala; Coto, Pedro B.; Lehnherr, Dan; Chernick, Erin; Papadopoulos, Ilias; Thoss, Michael; Tykwinski, Rik; Guldi, Dirk Michael (Nanoscale, 2016)
We show unambiguous and compelling evidence by means of pump-probe experiments, which are complemented by calculations using ab initio multireference perturbation theory, for intramolecular singlet fission (SF) within two synthetically tailored pentacene dimers with cross-conjugation, namely XC1 and XC2. The two pentacene dimers differ in terms of electronic interactions as evidenced by perturbation of the ground state absorption spectra stemming from stronger through-bond contributions in XC1 as confirmed by theory. Multiwavelength analysis, on one hand, and global analysis, on the other hand, confirm that the rapid singlet excited state decay and triplet excited state growth relate to SF. SF rate constants and quantum yields increase with solvent polarity. For example, XC2 reveals triplet quantum yields and rate constants as high as 162 ± 10% and (0.7 ± 0.1) × 1012 s-1, respectively, in room temperature solutions.
EAM Import::2019-03-13

Solvent-Dependent Singlet Fission in Diketopyrrolopyrrole Dimers: A Mediating Charge Transfer versus a Trapping Symmetry-Breaking Charge Separation - Papadopoulos, Ilias; Álvaro-Martins, Maria João; Molina, Desiré; McCosker, Patrick Michael; Keller, Paul A.; Clark, Timothy; Sastre-Santos, Ángela; Guldi, Dirk Michael (Advanced Energy Materials, 2020)
Three diketopyrrolopyrrole (DPP) dimers, linked via different dithienylphenylene spacers, ortho-DPP (o-DPP), meta-DPP (m-DPP), and para-DPP (p-DPP), are synthesized, characterized, and probed in light of intramolecular singlet fission (i-SF). Importantly, the corresponding DPP reference (DPP-Ref) singlet and triplet excited state energies of 2.22 and 1.04 eV, respectively, suggest that i-SF is thermodynamically feasible. The investigations focus on the impact of the relative positioning of the DPPs, and give compelling evidence that solvent polarity and/or spatial overlap govern i-SF dynamics and efficiencies. Polar solvents make the involvement of an intermediate charge transfer (CT) state possible, followed by the population of 1(T1T1) and subsequently (T1 + T1), while spatial overlap drives the mutual interactions between the DPPs. In o-DPP, the correct balance between polar solvents and spatial overlap leads to the highest triplet quantum yield (TQY) of 40%. Notable is the superimposition of CT and triplet excited states, preventing an accurate TQY determination. For m-DPP, poorer spatial overlap correlates with weaker CT character and manifests in a TQY of 11%. Strong CT character acts as a trap and prevents i-SF, as found with p-DPP. The DPP separation is decisive, enabling a symmetry-breaking charge-separated state rather than CT formation, shutting down the formation 1(T1T1).
CRIS-Team Scopus Importer:2020-10-09
Keywords: charge transfer states; diketopyrrolopyrrole dimers; intramolecular singlet fission

Varying the Interpentacene Electronic Coupling to Tune Singlet Fission - Papadopoulos, Ilias; Zirzlmeier, Johannes; Hetzer, Constantin; Bae, Youn J.; Krzyaniak, Matthew D.; Wasielewski, Michael R.; Clark, Timothy; Tykwinski, Rik; Guldi, Dirk Michael (Journal of the American Chemical Society, 2019)
We have designed and used four different spacers, denoted A-D, to connect two pentacenes and to probe the impact of intramolecular forces on the modulation of pentacene-pentacene interactions and, in turn, on the key steps in singlet fission (SF), that is, the 1 (S 1 S 0 )-to- 1 (T 1 T 1 ) as well as 1 (T 1 T 1 )-to- 5 (T 1 T 1 ) transitions by means of transient absorption and electron paramagnetic resonance measurements. In terms of the 1 (S 1 S 0 )-to- 1 (T 1 T 1 ) transition, a superexchange mechanism, that is, coupling to a higher-lying CT state to generate a virtual intermediate, enables rapid SF in A-D. Sizeable electronic coupling in A and B opens, on one hand, an additional pathway, that is, the population of a real intermediate, and changes, on the other hand, the mechanism to that of hopping. In turn, A and B feature much higher 1 (T 1 T 1 ) quantum yields than C and D, with a maximum value of 162% for A. In terms of the 1 (T 1 T 1 )-to- 5 (T 1 T 1 ) transition, the sizable electronic coupling in A and B is counterproductive, and C and D give rise to higher 5 (T 1 T 1 )-to-(T 1 + T 1 ) quantum yields than A and B, with a maximum value of 85% for D.
CRIS-Team Scopus Importer:2019-05-02